Divergent Response Strategies of CsABF Facing Abiotic Stress in Tea Plant: Perspectives From Drought-Tolerance Studies - Lu, Jing; Du, Jinke; Tian, Liying; Li, Mengshuang; Zhang, Xianchen; Zhang, Shihua; Wan, Xiaochun; Chen, Qi (Frontiers in Plant Science, 2021)
In plants, the bZIP family plays vital roles in various biological processes, including seed maturation, flower development, light signal transduction, pathogen defense, and various stress responses. Tea, as a popular beverage, is widely cultivated and has withstood a degree of environmental adversity. Currently, knowledge of the bZIP gene family in tea plants remains very limited. In this study, a total of 76 CsbZIP genes in tea plant were identified for the whole genome. Phylogenetic analysis with Arabidopsis counterparts revealed that CsbZIP proteins clustered into 13 subgroups, among which 13 ABFs related to the ABA signaling transduction pathway were further identified by conserved motif alignment and named CsABF1-13, these belonged to the A and S subgroups of CsbZIP and had close evolutionary relationships, possessing uniform or similar motif compositions. Transcriptome analysis revealed the expression profiles of CsABF genes in different tissues (bud, young leaf, mature leaf, old leaf, stem, root, flower, and fruit) and under diverse environmental stresses (drought, salt, chilling, and MeJA). Several CsABF genes with relatively low tissue expression, including CsABF1, CsABF5, CsABF9, and CsABF10, showed strong expression induction in stress response. Thirteen CsABF genes, were examined by qRT-PCR in two tea plant cultivars, drought-tolerant "Taicha 12" and drought-sensitive "Fuyun 6", under exogenous ABA and drought stress. Furthermore, CsABF2, CsABF8, and CsABF11, were screened out as key transcription factors regulating drought tolerance of tea cultivars. Subsequently, some potential target genes regulated by CsABFs were screened by co-expression network and enrichment analysis. This study update CsbZIP gene family and provides a global survey of the ABF gene family in tea plant. The resolution of the molecular mechanism of drought resistance in different varieties could be helpful for improving stress resistance in tea plant via genetic engineering.